Penggunaan Unconventional Weapons dalam Konflik Bersenjata Modern - Aldiansyach, Fadhillah Wahid Pramudya (Jurnal Hukum & Pembangunan, 2025)
The use of unconventional weapons such as cluster munitions, white phosphorus, nuclear weapons, artificial intelligence-based autonomous systems (AI/LAWS), and military neurotechnology is increasingly dominating modern armed conflicts. The characteristics of these weapons, particularly their widespread effects, uncertainty of control, and potential for automatic escalation, can pose serious challenges to the application of the principles of distinction and proportionality in International Humanitarian Law (IHL), especially when used in densely populated areas. The modernization of nuclear systems, the accelerated integration of AI into military command, and the emergence of neurotechnology indicate a regulatory gap that could potentially undermine humanitarian protection. This study uses a doctrinal (normative) method to interpret international legal instruments, examine doctrine and state practice, and review a number of empirical illustrations from Syria, Gaza, Ukraine, and regional military dynamics. The results of the study show that most unconventional weapons present inherent challenges in ensuring compliance with distinction and proportionality, mainly due to their uncontrollable destructive nature and algorithmic uncertainty in AI-based systems.